Levofloxacin plus Metronidazole Administered Once Daily versus Moxifloxacin Monotherapy against a Mixed Infection of Escherichia coli and Bacteroides fragilis in an In Vitro Pharmacodynamic Model - Hermsen, Elizabeth D. (American Society for Microbiology, 2005)
Moxifloxacin has been suggested as an option for monotherapy of intra-abdominal infections. Recent data support the use of a once-daily metronidazole regimen. The purpose of this study was to investigate the activity of levofloxacin (750 mg every 24 h [q24h]) plus metronidazole (1,500 mg q24h) compared with that of moxifloxacin (400 mg q24h) monotherapy in a mixed-infection model. By using an in vitro pharmacodynamic model in duplicate, Escherichia coli and Bacteroides fragilis were exposed to peak concentrations of 8.5 mg of levofloxacin/liter q24h, 32 mg of metronidazole/liter q24h, and 2 mg for moxifloxacin/liter q24h for 24 h. The activities of levofloxacin, metronidazole, moxifloxacin, and levofloxacin plus metronidazole were evaluated against E. coli, B. fragilis, and E. coli plus B. fragilis. The targeted half-lives of levofloxacin, metronidazole, and moxifloxacin were 8, 8, and 12 h, respectively. Time-kill curves were analyzed for time to 3-log killing, slope, and regrowth. Pre- and postexposure MICs were determined. The preexposure levofloxacin, metronidazole, and moxifloxacin MICs for E. coli and B. fragilis were 0.5 and 1, >64 and 0.5, and 1 and 0.25 mg/liter, respectively. Levofloxacin and moxifloxacin achieved a 3-log killing against E. coli and B. fragilis in all experiments, as did metronidazole against B. fragilis. Metronidazole did not decrease the starting inoculum of E. coli. The area under the concentration-time curve/MIC ratios for E. coli and B. fragilis were 171.7 and 85.9, respectively, for levofloxacin and 26 and 103.9, respectively, for moxifloxacin. Levofloxacin plus metronidazole exhibited the fastest rates of killing. The levofloxacin and moxifloxacin MICs for B. fragilis increased 8- to 16-fold after the organism was exposed to moxifloxacin. No other changes in the postexposure MICs were found. Levofloxacin plus metronidazole administered once daily exhibited activity similar to that of moxifloxacin against the mixed E. coli and B. fragilis infection. A once-daily regimen of levofloxacin plus metronidazole looks promising for the treatment of intra-abdominal infections.